Implementasi Metode Drill Dalam Peningkatan Hasil Belajar Pada Materi Hukum Mawaris Di Mts Al-Ijtihadiyah Martebing - Zanna Ika Pramesti (Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to find out how to improve student learning outcomes in mawaris law material at MTs Al-Ijtihadiyah Martebing and to find out how student learning outcomes after the teacher applies the drill method to mawaris law subjects. The method used in this study uses descriptive qualitative analysis methods. The subjects of this study were students of class IX-D MTs Al-Ijtihadiyah Martebing in the 2019/2020 Academic Year, totaling 30 people. The results of this study can be seen that the increase in student learning outcomes in mawaris law material has increased significantly. This can be seen from the initial data value of students who completed there were about 10 people the percentage was 33.33%, while students who did not complete about 20 people had a percentage of 66.67%. On the results of tests of students who completed about 22 people the percentage was 73.33%, while students who did not complete were about 8 people the percentage was 26.67%. So that it experienced a significant increase of around 50%. From the results above it can be concluded that student learning outcomes have increased. Keywords: Drill Method and Learning Outcomes